Determination of awareness, attitude and sensitiveness of dog owners and levels of understanding of dog body language - Seker, Ibrahim; Erten, Omer; Koseman, Abdurrahman (Univ Zulia, Facultad Ciencias Veterinarias, 2023)
This research was carried out to determine the identification of the awareness, attitude and sensitiveness of dog owners in Turkiye, and levels of understanding the body language of dogs. The research material consisted of data obtained from face-to-face surveys with randomly selected 172 dog owners. In the study, the differences between the education level categories of dog owners were found to be statistically significant (P<0.01), but not for marital status, child ownership, age and household income (P>0.05). In addition, the rate of those who did not have children was found to be higher among those who adopted dogs for the reasons of animal love/compassion (58.6%) and feeling of loneliness (75.0%). According to the findings, dog owners spend a maximum of 1-2 hours with their dogs during the day. Men have more difficulty in caring for their dogs than women due to lack of time, financial constraints and other reasons. In this study, dog owners were able to correctly identify 10 of the 20 images of dog body language at a medium and high level (50.0-95.3%), and 10 of them at a low and very low level (47.7-4.1%). As a result; It is important for those who want to have a dog to make an attempt by questioning whether they have the necessary time, energy and financial means. In addition, it is thought that it is important to learn the body language of dogs, that there is a need for institutional structures that will help people who own or want to acquire dogs in this regard and in the field of general breeding, and teach them the requirements of their responsibilities.
Determinación de la conciencia, actitud y sensibilidad de los dueños de perros y niveles de comprensión del lenguaje corporal del perro
Keywords: Awareness; dog body language; dog owner; attitude